When kids can't read, what teachers can do : a guide for teachers, 6-12 - Beers, G. Kylene, 1957- (Portsmouth, NH : Heinemann, 2003)
For Kylene Beers, the question of what to do when kids can't read surfaced in 1979 when she met and began teaching a boy named George. When George's parents asked her to explain why he couldn't read and how she could help, Beers, a secondary certified English teacher with no background in reading, realized she had little to offer. That moment sent her on a twenty-three-year search for answers to the question: How do we help middle and high schoolers who can't read? Now, she shares what she has learned and shows teachers how to help struggling readers with comprehension, vocabulary, fluency, word recognition, and motivation. Filled with student transcripts, detailed strategies, reproducible material, and extensive booklists, Beers' guide to teaching reading both instructs and inspires.
A defining moment -- Creating independent readers -- Assessing dependent readers' needs -- Explicit instruction in comprehension -- Learning to make inference -- Frontloading meaning: pre-reading strategies -- Constructing meaning: during reading strategies -- Extending meaning: after-reading strategies -- Vocabulary: figuring out what words mean something -- Fluency and automaticity: the rhythm of reading -- Word recognition: what's after "sound it out?" -- Spelling: from word lists to how words work -- Creating the confidence to respond -- Finding the right book -- A final letter to George.
Includes bibliographical references (p. 369-378) and index.
Keywords: Reading -- Remedial teaching; Reading (Middle school); Reading (Secondary)